Assessment of geography learning process standards in the indonesian curriculum: Instrument development and quality - Amalia, Tuti; Nursa'ban, Muhammad (Jurnal Penelitian dan Evaluasi Pendidikan, 2023)
The need for mapping the achievement of geography learning process standards in the Indonesian curriculum can provide recommendations in accordance with the conditions in the field. This study aims to determine and describe the quality of geography learning process standard instruments in the Indonesian curriculum, namely: 1) content validity 2) construct validity 3) reliability. This research is instrument development research. The development stage used is the development stage of the instrument test by Heri Retnawati. The process of preparing the instrument, namely: determining the purpose of instrument preparation, searching for relevant theories, compiling indicators of instrument items, compiling instrument items, content validation, revising based on expert input, conducting trials to respondents, conducting reliability analysis, and assembling instruments by considering certain characteristics. The data analysis used was content validity with the Aiken method, construct validity with Exploratory Factor Analysis (EFA), and reliability with the Cronbach Alpha formula. The results of this study showed that: 1) The standard instrument of geography learning process in Indonesian curriculum based on Aiken's V index value of 0.92 is categorized as high. 2) The standard geography learning process instrument in the Indonesian curriculum using EFA formed into eight factors can explain the variance of 73.452%. 3) Reliability estimation results on the standard instrument of geography learning process in the Indonesian curriculum amounted to 0.913 very high category. This research is expected to be an appropriate recommendation for the follow-up of geography learning process standards in the Indonesian curriculum.